Effects and mechanism of dexmedetomidine on neuronal cell injury induced by hypoxia-ischemia - Liu, Ya-Jun; Wang, Duan-Yu; Yang, Yong-Jian; Lei, Wei-Fu (BMC anesthesiology, 2017)
The present study aims to investigate the protective effects of dexmedetomidine (DMED) on hypoxia ischemia injury induced by oxygen and glucose deprivation (OGD) in PC12 and primary neuronal cells. PC12 cells exposed to OGD was used to establish ischemia model. The OGD-induced cell injury was evaluated by alterations of cell viability, apoptosis and expressions of apoptosis-associated proteins. Oxidative stress and expressions of neurotrophic factors after OGD and DMED treatments were also explored. The activation of possible involved signaling pathways were studied after OGD and DMED treatments, along with the addition of inhibitors of these pathways. Finally, the effects of DMED on primary neuronal cells were verified according to the alterations of inflammatory cytokines release and oxidative stress. DMED obviously increased cell viability and reduced cell apoptosis as well as ratio of Bax/Bcl-2 in OGD-treated PC12 cells. Then, the OGD-induced changes of LDH, MDA, SOD and GSH-Px as well as decreases of neurotrophic factors were all ameliorated by DMED treatment. Key kinases in Notch/NF-κB signaling pathway were up-regulated by OGD, whereas the up-regulations were decreased by DMED. In addition, inhibitor of Notch or NF-κB could augment the effects of DMED on OGD-induced cell injury. Finally, the protective effects of DMED were verified in primary neuronal cells. DMED had protective effect on OGD-induced PC12 cell injury, depending on its anti-apoptotic, anti-oxidative activity and the inhibition of Notch/NF-κB activation. Our findings suggested that DMED could be used as a potential therapeutic drug for cerebral ischemia.